PSGL-1 Is a T Cell Intrinsic Inhibitor That Regulates Effector and Memory Differentiation and Responses During Viral Infection - Tinoco, Roberto; Neubert, Emily N.; Stairiker, Christopher J.; Henriquez, Monique L.; Bradley, Linda M. (Frontiers in Immunology, 2021)
Effective T cell differentiation during acute virus infections leads to the generation of effector T cells that mediate viral clearance, as well as memory T cells that confer protection against subsequent reinfection. While inhibitory immune checkpoints have been shown to promote T cell dysfunction during chronic virus infections and in tumors, their roles in fine tuning the differentiation and responses of effector and memory T cells are only just beginning to be appreciated. We previously identified PSGL-1 as a fundamental regulator of T cell exhaustion that promotes expression of several inhibitory receptors, including PD-1. We now show that PSGL-1 can restrict the magnitude of effector T cell responses and memory T cell development to acute LCMV virus infection by limiting survival, promoting PD-1 expression, and reducing effector responses. After infection, PSGL-1-deficient effector T cells accumulated to a greater extent than wild type T cells, and preferentially generated memory precursor cells that displayed enhanced survival and functional capacity as persisting memory cells. However, as memory cells, they failed to respond to a homologous virus challenge after adoptive transfer into naïve hosts indicating an impaired capacity to generate memory effector T cell responses. These studies underscore the function of PSGL-1 as a key negative regulator of effector and memory T cell differentiation and suggest that PSGL-1 may limit excessive stimulation of memory T cells during viral infection by promoting inhibitory signaling.